Overcoming theoretical stagnation through cultural–historical neuropsychology: The case of dyslexia. (April 2022) - Solovieva, Yulia; Koutsoklenis, Athanasios; Quintanar, Luis
In this article we argue that cultural–historical neuropsychology manages to escape the theoretical stagnation that characterises the field of dyslexia. To support our argumentation, we first define cultural–historical psychology and neuropsychology and determine their subject matter. Afterwards, we provide an outline of how reading and reading difficulties are perceived through the prism of cultural–historical neuropsychology. We then discuss several mainstream conceptualisations of dyslexia that contribute to the theoretical stagnation in the field. Finally, we explain how cultural–historical neuropsychology avoids each theoretical barrier imposed by mainstream conceptualisations.